RANCANG BANGUN SISTEM INFORMASI KONSULTASI DAN PENJADWALAN FISIOTERAPI PENYAKIT BELL’S PALSY (STUDI KASUS KLINIK GRIYA FISIOTERAPIS) - Rejalana Bayu Kurniawan; Nadiyasari Agitha; Royana Afwani (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2021)
AbstractBell's palsy is an acute paralysis of the prifer facial nerve of unknown cause and results in permanent disability ifnot treated properly. In this study, Development of Consultation Information System Scheduling Bell’s Palsy Diseasewas designed and built which can help in overcoming physiotherapy scheduling as well as recording medicalrecords, so that they can be well controlled and coordinated. The development method in information systems isdesigned using the RUP (Rational Unified Process) method, where testing using the RUP method is carried out usingblack box testing and using usability (questionnaires). In black box testing, the result is 1, which means that allfeatures are running correctly. In the usability test, the results obtained were 92.30% which was stated relativelyfeasible because the test was carried out on a physiotherapist, and 87.03% which was carried out with 30respondents who met the usability standard referred to in table I, namely the table of score interpretation criteriaor declared